Multiple Sclerosis: Melatonin, Orexin, and Ceramide Interact with Platelet Activation Coagulation Factors and Gut-Microbiome-Derived Butyrate in the Circadian Dysregulation of Mitochondria in Glia and Immune Cells - Anderson, George (Int J Mol Sci, 2019)
Recent data highlight the important roles of the gut microbiome, gut permeability, and alterations in mitochondria functioning in the pathophysiology of multiple sclerosis (MS). This article reviews such data, indicating two important aspects of alterations in the gut in the modulation of mitochondria: (1) Gut permeability increases toll-like receptor (TLR) activators, viz circulating lipopolysaccharide (LPS), and exosomal high-mobility group box (HMGB)1. LPS and HMGB1 increase inducible nitric oxide synthase and superoxide, leading to peroxynitrite-driven acidic sphingomyelinase and ceramide. Ceramide is a major driver of MS pathophysiology via its impacts on glia mitochondria functioning; (2) Gut dysbiosis lowers production of the short-chain fatty acid, butyrate. Butyrate is a significant positive regulator of mitochondrial function, as well as suppressing the levels and effects of ceramide. Ceramide acts to suppress the circadian optimizers of mitochondria functioning, viz daytime orexin and night-time melatonin. Orexin, melatonin, and butyrate increase mitochondria oxidative phosphorylation partly via the disinhibition of the pyruvate dehydrogenase complex, leading to an increase in acetyl-coenzyme A (CoA). Acetyl-CoA is a necessary co-substrate for activation of the mitochondria melatonergic pathway, allowing melatonin to optimize mitochondrial function. Data would indicate that gut-driven alterations in ceramide and mitochondrial function, particularly in glia and immune cells, underpin MS pathophysiology. Aryl hydrocarbon receptor (AhR) activators, such as stress-induced kynurenine and air pollutants, may interact with the mitochondrial melatonergic pathway via AhR-induced cytochrome P450 (CYP)1b1, which backward converts melatonin to N-acetylserotonin (NAS). The loss of mitochnodria melatonin coupled with increased NAS has implications for altered mitochondrial function in many cell types that are relevant to MS pathophysiology. NAS is increased in secondary progressive MS, indicating a role for changes in the mitochondria melatonergic pathway in the progression of MS symptomatology. This provides a framework for the integration of diverse bodies of data on MS pathophysiology, with a number of readily applicable treatment interventions, including the utilization of sodium butyrate.